MENYISIPKAN NILAI-NILAI AGAMA DALAM PEMBELAJARAN SAINS: Upaya Alternatif Memagari Aqidah Siswa - Tomo Djudin (The Pontianak State Institute of Islamic Studies, 2011)
Most of natural science teachings and science textbooks used in the schools were lack of religious values that enable to enhance students’ faith of God, the creator of the universe. Integrating and providing the Islamic spirits or religious values to the teaching-learning processes of products of science (facts, concepts, and principles) should be undertaken. By this way, we hope, materialism or secularism point of views could be eliminated. It is not a science teacher task, but ours as moslems as well.